1997
DOI: 10.1126/science.275.5305.1452
|View full text |Cite
|
Sign up to set email alerts
|

Strontianite in Coral Skeletal Aragonite

Abstract: An x-ray spectroscopic study of scleractinian coral skeletons indicated that, although some strontium substitutes for calcium in the aragonite structure, at concentrations of about 7500 parts per million, as much as 40 percent of the strontium resides in strontianite (SrCO3). A doublet peak in the Fourier transform of the extended x-ray absorption fine structure of the coral corresponded to six metal and 13 oxygen neighbors surrounding strontium at about 4.05 angstroms in strontium-substituted aragonite and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 12 publications
5
58
0
Order By: Relevance
“…Uptake of elements from the diet, however, may follow completely different principles. In corals, strontium is incorporated not only through a simple ion substitution for Ca, but to a considerable amount as strontianite (SrCO 3 ) (Greegor et al 1997; but for a different view see: Finch et al 2003). Since strontium concentrations in corals are similar to those in cephalopod statoliths, such a mechanism seems possible for these aragonite-dominated structures as well.…”
Section: Discussionmentioning
confidence: 99%
“…Uptake of elements from the diet, however, may follow completely different principles. In corals, strontium is incorporated not only through a simple ion substitution for Ca, but to a considerable amount as strontianite (SrCO 3 ) (Greegor et al 1997; but for a different view see: Finch et al 2003). Since strontium concentrations in corals are similar to those in cephalopod statoliths, such a mechanism seems possible for these aragonite-dominated structures as well.…”
Section: Discussionmentioning
confidence: 99%
“…Amiel et al (1973) suggested that strontium in the coral lattice framework replaces calcium and that strontium associated with organic compounds is negligible in aragonite corals. Recently, using an X-ray spectroscopic study of coral skeletons, Greegor et al (1997) found 40% of strontium present as strontianite (SrCO 3 ) and 60% strontium substituted for calcium in aragonite structures. Their results indicate that mechanisms of strontium incorporation into coral are unexpectedly complex and that the temperature-sensitive partitioning of strontium between seawater and coral skeleton require further works.…”
Section: Sr/ca Ratiomentioning
confidence: 99%
“…These fluctuations are not observed in coral Sr/Ca records generated using bulk sampling techniques, which are too coarse to resolve subseasonal variability. The apparent heterogeneity in Sr/Ca distribution within coral skeleton has been attributed to variations in calcification rate [Weber, 1973], the presence of organic matrix [Allison, 1996] and strontianite [Greegor et al, 1997] and to physiological processes linked to coral spawning [Meibom et al, 2003]. Cohen et al [2001] noted that biweekly oscillations in Sr/Ca of a Pacific Porites appeared to match smaller oscillations in the in situ SST record.…”
Section: Introductionmentioning
confidence: 99%